Organoleptic Quality of Chicken Nugget with Broccoli (Brassica oleracea L.) and Carrot (Daucus carota L.) Addition - Riskayanti, Riskayanti; Hikmah, Hikmah; Said, Muhammad Irfan; Nahariah, Nahariah (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2023)
This study aimed to determine the effect of cooking and level of vegetable addition and their interaction on the organoleptic quality of chicken nuggets. The research design consisted of 2 factors: the first factor was vegetable cooking treatment (fresh and steamed), and the second factor was vegetable addition level (0%, 5%, 10%, and 15%). The parameters measured were the organoleptic quality of chicken nuggets (color, texture, aroma, taste, t and acceptance/hedonic). The results showed that cooking treatment had no effect (P>0.05) on the organoleptic quality of nuggets, but the level of vegetable addition affected (P<0.05) the organoleptic quality of nuggets. Increasing the level of vegetable addition decreased the color value of L*, a*, but increased the color of b*. Besides, the organoleptic test decreased the attribute scores of color, aroma, taste, and texture but was still accepted by panelists up to 15% vegetable addition level. There was no interaction between cooking treatment and the level of vegetable addition on the organoleptic quality of nuggets. From this study, it can be concluded that the best treatment is using fresh vegetables up to 15% addition level. Keyword: Chicken Meat, Broccoli, Carrot, Chicken Nuggets, Organoleptic